Another World: A Retreat in the Ozarks - Claassen, William (Rowman & Littlefield Publishers, 2007)
Another World explores day to day life in a small Trappist monastery tucked away in the Ozark foothills. Interweaving memoir with conversations with the monks, observations of community life, and relationships with other visitors, Claassen provides a window into contemporary monastic life. Each chapter describes a day in the monastery. The reading experience is like spending time away from the world in a real community that is very human and gently inspiring. Eighteen black & white photos by the author further evoke the experience.